COMPOUND WORD IN INTERNET DATING TERMS - Habibah, Husnun; Tawami, Tatan (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
In this study the authors analyzed the Compound Word in Internet Dating Terms. The author focuses on analyzing the merge of words from existing words to rise the new words/meanings or can also be referred as compounding. The data taken by the author are the words that exist in the term of internet dating by taking examples from cases in social media, namely Twitter. Examples of data cases taken by the author are calculated from March 31, 2020 - March 31, 2022. The method used in this study is descriptive analysis. According to Rakhmat (68), descriptive research method is a research method that only describes situations/events but also explain the data systematically. In researching the selected data, the writer classified the data based on the elements that make up words/expressions on internet dating by focusing on Endocentric and Exocentric Compound. From the analysis, it can be concluded that compound words in internet dating terms were formed mostly by free morphemes, most compound words were not compositional. This means that most compound words are exocentric. Keywords: Compounding, Exocentric, Endocentric, Internet dating